Titanium Silicide Coated Porous Silicon Nanospheres as Anode Materials for Lithium Ion Batteries. (1st January 2015) - Kim, Young Min; Ahn, Jihoon; Yu, Seung-Ho; Chung, Dong Young; Lee, Kyung Jae; Lee, Jin-Kyu; Sung, Yung-Eun
Highlights: We have developed a facile synthesis method for producing P-Si@TiSi2 nanospheres by magnesiothermic reduction. P-Si@TiSi2 composites exhibit a large reversible capacity approximately 1180 mAh g −1 even after 50 cycles. P-Si@TiSi2 composites exhibit a significantly enhanced electrochemical performance compared to that of pure Si. Abstract: We report on the facile synthesis of porous silicon structure via magnesiothermic reduction followed by coating of the surface with TiSi2 . These modifications not only showed significant promise in overcoming the drastic volume change during charge and discharge cycles but also in improving the relatively low conductivity of silicon. The synthesized porous structure with a highly electrically conductive coating layer significantly enhanced the electrochemical performance in terms of cyclic stability and rate capability. The TiSi2 coating layer, which has good electrical conductivity and physical strength, enhances the conductivity and maintains the Si structure during cycling. This combination of porous structure via magnesiothermic reduction and highly conductive TiSi2 coating provides a synergistic effect, which can be seen in the improvements in electrochemical performance. This synthesis demonstrates a promising method for producing high capacity anode materials for next generation LIBs.